Pengaruh Elevasi Ekstremitas Atas dan Teknik Napas Dalam terhadap Penurunan Nyeri Area Insersi Radialis pada Pasien Post Up Sheath Kateterisasi Jantung di RS Dr. Mohammad Hoesin Palembang - Andry Mayanto; Azizah Khoiriyati (Borneo Nursing Journal (BNJ), 2026)
Pain at the sheath insertion site is a common complaint among patients after cardiac catheterization, caused by tissue trauma, mechanical pressure during hemostasis, and post-procedural limb immobilization. This study aimed to determine the effect of upper extremity elevation and deep breathing techniques on pain reduction in post-up sheath cardiac catheterization patients at Dr. Mohammad Hoesin Hospital Palembang. This study used a quasi-experimental design with a pre-test and post-test control group approach, involving 50 respondents divided into an intervention group and a control group of 25 respondents each, selected through simple random sampling. The intervention group received 30° upper extremity elevation for 10 minutes combined with five cycles of deep breathing, while the control group received standard care. Pain level was measured using the Numeric Rating Scale (NRS) and analyzed using the Wilcoxon and Mann-Whitney tests. The results showed that the mean pain level in the intervention group decreased from 3.24 to 1.52 (a reduction of 1.72; p=0.000), while in the control group it decreased from 2.80 to 2.64 (a reduction of 0.16; p=0.046). The Mann-Whitney test on the pain score difference showed that the reduction in the intervention group was significantly greater than in the control group (p=0.000). It can be concluded that upper extremity elevation and deep breathing techniques significantly affect the reduction of radial insertion site pain in post-up sheath cardiac catheterization patients and can be applied as a complementary nonpharmacological intervention to improve patient comfort after the procedure.